Field screening and identification of stable resistance sources in wheat germplasm against loose smut disease caused by Ustilago segetum var. tritici - Kumar, Sudheer; Kashyap, Prem Lal; Singh, Ishwar; Jasrotia, Poonam; Singh, Gyanendra Pratap (Journal of Cereal Research, 2025)
Loose smut (LS) caused by Ustilago segetum var. tritici is an important disease of wheat (Triticum spp.) and accounts for 1-2% annual yield losses in India. The disease can be managed easily with the use of seed treatment with systematic fungicides, however, the application of these fungicides remained limited amongst farmers mainly due to their high price, limited knowledge about seed protectants as well as lack of any visible external symptoms on infected seeds. Additionally, seed dressing with protectants is hazardous to the environment and human health and thus not acceptable in organic wheat cultivation. The most affordable and environment friendly technique to protect wheat crop is to develop varieties that are resistant to loose smut disease. Therefore, research efforts have been made to screen one hundred and ninety-seven wheat genotypes obtained from gene bank (Germplasm resource unit, ICAR-Indian Institute of Wheat and Barley Research) under field conditions for LS disease using artificial inoculation technique. The experiment was laid out in randomized block design with three replications for two consecutive years during 2014-15 and 2015-21016. The results of the field trials indicated that only seventy seven genotypes (39.09 %) showed resistance to loose smut and infection ranged from 0-5% under artificially inoculated conditions. More than 15 % genotypes (31) were found to be immune and 18.78 % (thirty seven) genotypes were highly resistant (HR) and twenty three (11.68%) were identified as susceptible (S) genotypes. There was forty-nine moderately susceptible genotype obtained from the experiment. The results reveled that there are some promising LS resistance lines and could therefore be introduced to wheat breeders for further breeding as well as multi-locational trials for developing disease-resistant cultivars.